Review to the Level of Minerals in Teff [Eragrostis tef (Zuccagni) Trotter], Grain Samples - Awulachew, Melaku Tafese (International Journal For Research In Agricultural And Food Science, 2019)
Tef (Eragrostis tef (Zucc.) Trotter) is a fine grain that comes in a variety of colors, from white and red to dark brown. Tef grown in Ethiopia predominantly is used to make injera, flatbread or flat pancake like fermented bread. Globally it is being found in health food stores for its long least of health benefits. Tef is leading all cereal grains by a wide margin having a high concentration of a variety of nutrients, most of which are easily absorbed by human body at most. Such as in mineral nutrients including calcium, thiamin, iron, copper, zinc, aluminum, molybdenum, barium and silicon oxide; and amino acids such as phenylalanine, tyrosine, threonine, histidine and methionine. Outside Ethiopia there is a growing interest in using tef, usually being found in health food stores either in the grain form or ground into flour, for a long list of health benefits. It is an excellent gluten-free flour alternative, and being used to make pie crusts, cookies, breads, and an assortment of other baked goods.